The Boost study: design of a school- and community-based randomised trial to promote fruit and vegetable consumption among teenagers - Krølner Rikke; Suldrup Jørgensen Thea; Aarestrup Anne; Hjøllund Christiansen Anne; Christensen Anne; Due Pernille (BMC, 2012)
Abstract Background The aim of the Boost study was to produce a persistent increase in fruit and vegetable consumption among 13-year-olds. This paper describes the development, implementation and evaluation of a school-and community-based, multi-component intervention guided by theory, evidence, and best practice. Methods/design We used the Intervention Mapping protocol to guide the development of the intervention. Programme activities combined environmental and educational strategies and focused on increasing access to fruit and vegetables in three settings: School: Daily provision of free fruit and vegetables; a pleasant eating environment; classroom curricular activities; individually computer tailored messages; one-day-workshop for teachers. Families: school meeting; guided child-parent activities; newsletters. Local community: guided visits in grocery stores and local area as part of classroom curriculum; information sheets to sports-and youth clubs. The Boost study employed a cluster-randomised controlled study design and applied simple two-stage cluster sampling: A random sample of 10 municipalities followed by a random sample of 4 schools within each municipality (N = 40 schools). Schools were randomised into a total of 20 intervention-and 20 control schools. We included all year 7 pupils except those from school classes with special needs. Timeline: Baseline survey: August 2010. Delivery of intervention: September 2010-May 2011. First follow-up survey: May/June 2011. Second follow-up survey: May/June 2012. Primary outcome measures: Daily mean intake of fruit and vegetables and habitual fruit and vegetable intake measured by validated 24-hour recall-and food frequency questionnaires. Secondary outcome measures: determinants of fruit and vegetable intake, positive side-effects and unintended adverse effects. Implementation was monitored by thorough process evaluation. Discussion The baseline data file included 2,156 adolescents (95%). There was baseline equivalence between intervention-and control groups for sociodemographics, primary outcomes, and availability at home, school and sports-and youth clubs. Significantly larger proportions of pupils in the control group had parents born in Denmark. The study will provide insights into effective strategies to increase fruit and vegetable intake among teenagers. The study will gain knowledge on implementation processes, intervention effects in population subgroups with low intake, and opportunities for including local communities in interventions. Trial registration Current Controlled Trials ISRCTN11666034.